Study on the Performance of an Alpha Energy Spectrum Radon Measuring Instrument Based on CdZnTe Detector. Issue 2 (August 2021) - Li, Songsong; Shan, Jian; Tan, Songbo
Abstract : Abstract: To realize a fast and reliable approach for continuous radon measurements, a CdZnTe (CZT) detector based on the electrostatic collection method was developed. The experimental results show that when the external temperature varies from 5 °C to 30 °C, the maximum drifts of the characteristic peak positions of 218 Po and 214 Po are only 8 and 6. Furthermore, the measurement error associated with the constant radon concentration is less than 5.5%. As the temperature increases or decreases, the measurement error becomes larger, with the maximum error being 43.1%. The response of the proposed instrument for constant radon concentration is better than that of the RAD7 radon measurement instrument. At 25 °C, the value measured using the NRL-II radon meter with the PIPS detector is in good agreement with the actual value. The new radon measurement instrument exhibits a good compliance from the third measurement cycle (measurement deviation 0.53–3.95%), while RAD7 has good compliance from the fourth measurement cycle (measurement deviation of 1.17–4.88%). The theoretical and practical values of the iterative correction factor (influence of the previous measurement on the current measurement) of the radon measurement instrument are in good agreement. The iterative correction factor can be used for performing continuous radon measurements independently, with the aim of achieving a rapid response to environmental radon concentrations.